PENERAPAN MODEL INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 167 PEKANBARU - Siti Rumini; Zulkifli '; Hamizi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research aims to increase the student’s IPA outcomes at 4th grade in elementary school 167 Pekanbaru by using inquiry learning model. Problems that occur in school are a) students easily discouraged in solving the problems that the teacher and see the result of his work, b) Most of the students passive in the learning process, students are less able to dig his own knowledge, c) Smart student don’t want to help students weak in the learning process, especially in group discussion activities. The subject in this research are 4th grade that totally is 40 who is 24 male students and 16 female students. Object in the research is to increase the student’s IPA outcomes by using inquiry learning model at 4th grade in elementary school 167 Pekanbaru. This research is two cycles, the each cycle consisting of two meetings and test. The average percentage of the students is increased 70% in the first cycle and increase 82.5% in the second cycle, before using the model is 55%. The average student’s learning outcomes increase from base score to first cycle is 5.9% , the second cycle average student’s learning outcomes is 13.8%. Basically the student’s learning outcomes can be show of inquiry learning model can to increase the student’s IPA outcomes at 4th grade in elementary school 167 Pekanbaru.Keywords: Inquiry Learning Model, IPA learning outcomes